1996
DOI: 10.1084/jem.183.3.1265
|View full text |Cite
|
Sign up to set email alerts
|

An immunoglobulin E-dependent recombinant histamine-releasing factor induces interleukin-4 secretion from human basophils.

Abstract: SummaryA novel recombinant histamine-releasing factor (rHFR), which stimulates secretion from a subpopulation of human basophils that express a particular type of immunoglobuhn E (IgE) or IgE +, was found to induce interleukin-4 (IL-4) production from cells isolated from these same donors. The secretion of IL-4 protein induced by rHRF significantly correlated with histamine release and the amount of protein generated, and the kinetics were identical to those caused by anti-IgE activation. Furthermore, the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…11,38,[40][41][42][43][44][45] A 21-kDa histamine-releasing factor, whose action appears to be IgE-dependent, is also a complete stimulus for basophil mediator release, but it is active only on basophils from approximately 50% of individuals. [46][47][48] Our study therefore not only identifies LIR7 as a novel signaling receptor on human basophils, but also identifies activation through LIR7 as the only presently identified IgE-independent complete stimulus for human For personal use only. on March 28, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…11,38,[40][41][42][43][44][45] A 21-kDa histamine-releasing factor, whose action appears to be IgE-dependent, is also a complete stimulus for basophil mediator release, but it is active only on basophils from approximately 50% of individuals. [46][47][48] Our study therefore not only identifies LIR7 as a novel signaling receptor on human basophils, but also identifies activation through LIR7 as the only presently identified IgE-independent complete stimulus for human For personal use only. on March 28, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between HC and PC IgEs is reminiscent of the dichotomy found in human IgE molecules in their ability to prime basophils for the stimulation with histamine-releasing factor, a cytokine produced by macrophages and platelets: basophils bound by IgEs (termed IgE ϩ ) derived from atopic patients, but not those (termed IgE Ϫ ) from normal subjects, can release histamine and cytokines such as IL-4 and IL-13 in response to histamine-releasing factor (83,84). Structural basis for the difference between IgE ϩ and IgE Ϫ is not known yet.…”
Section: In Vivo Effects Of Ige(-ag) Stimulation and Their Implicatiomentioning
confidence: 99%
“…HRF/TCTP was initially described as a complete secretagog for histamine and IL-4 secretion from basophils of certain allergic donors. 15 Initially, it was thought that these donors had a certain type of IgE that interacted with HRF/TCTP to induce secretion. 15 However, it was subsequently demonstrated that HRF/TCTP primed HRF/TCTP non-responder (HRF/TCTP-NR) basophils for histamine release as well as IL-4 and IL-13 secretion regardless of the type of IgE.…”
mentioning
confidence: 99%